2012
DOI: 10.1590/s1413-35552012005000019
|View full text |Cite
|
Sign up to set email alerts
|

Self-controlled feedback enhances learning in adults with Down syndrome

Abstract: Background: One factor that has consistently been shown to enhance learning in typical participants is self-controlled practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 51 publications
3
19
0
5
Order By: Relevance
“…Consequently, this leads to the quick identification of the existing relationships among the components of the feedback (Guadagnoli & Kohl, 2001). However, the noteworthy point in the current study and the studies done about the motivational feedback such as self-controlled feedback (Chiviacowsky & Wulf, 2005;Chiviacowsky, Wulf, de Medeiros, Kaefer, & Tani, 2008;Chiviacowsky, Wulf, Machado, & Rydberg, 2012) and good and poor trials (Badami et al, 2012;Saemi et al, 2011) contained the lasting effect of this kind of feedback in the retention tests of doing tasks. The findings showed that those who received feedback after their good trials in the retention tests scored better than those who received feedback after their poor trials.…”
Section: Discussionmentioning
confidence: 49%
“…Consequently, this leads to the quick identification of the existing relationships among the components of the feedback (Guadagnoli & Kohl, 2001). However, the noteworthy point in the current study and the studies done about the motivational feedback such as self-controlled feedback (Chiviacowsky & Wulf, 2005;Chiviacowsky, Wulf, de Medeiros, Kaefer, & Tani, 2008;Chiviacowsky, Wulf, Machado, & Rydberg, 2012) and good and poor trials (Badami et al, 2012;Saemi et al, 2011) contained the lasting effect of this kind of feedback in the retention tests of doing tasks. The findings showed that those who received feedback after their good trials in the retention tests scored better than those who received feedback after their poor trials.…”
Section: Discussionmentioning
confidence: 49%
“…Likewise Chiviacowisky et al [8] found that the frequency of knowledge of results (KR) did not influence the learning of motor skills in patients with Down syndrome. In their study a group of individuals with DS received 100% of the KR and another 33% both in the acquisition phase and after a 48-hour retention phase during which KR was not supplied; the results showed no difference between groups.…”
Section: /10mentioning
confidence: 97%
“…There are some authors studying the motor learning area in DS like, Chiviacowsky et al [6,8] that showed the effect of knowledge of frequencies on motor learning in adults with DS; Bussy et al [9] compared the perceptual learning of individuals with Fragile X and DS; Possebom et al [10] studied motor learning in this population with the help of a maze task on the computer, and Ringenbarch et al [11] attempted to understand how people with DS perform the different tasks of continuous drumming and unimanual drumming. This is a new approach and has been many used, and this seems to be very interesting considering the advances in technology and also being an instrument that can make feasible tasks in computing environments.…”
Section: Introductionmentioning
confidence: 99%
“…They sometimes require longer practice time and experience of a task, and so are able to improve their performance, developing learning skills and autonomy/self-control, which is based on concepts of neural plasticity and motor learning principles (Chiviacowsky, Wulf, Machado, & Rydberg, 2012;Berg, Becker, Martian, Primrose, & Wingen, 2012;Gimenez, Manoel, & Basso, 2006). According to this study, the intervention with hippotherapy sessions, in which they were subjected to the movement of the horse for 30 minutes per session, generating postural adjustments in practitioners with DS and no physical impairment led to the acquisition of motor skills through practice, resulting in better control of muscle activation of lower limbs.…”
Section: Acta Scientiarum Health Sciencesmentioning
confidence: 99%